The imagination gap - Reich, Brian, 1977- (Emerald Publishing Limited, 2017)
Imagination provides a window into the world of what is possible helping us to navigate in times of uncertainty and come up with new ideas. Everyone has an imagination but most do not use our imaginations to their fullest potential or apply our imaginations to the challenges that we face. Our most important ideas and biggest ambitions never turn in to reality. In this timely new book, Brian Reich shows us that imagination is one of the most powerful forces in shaping and motivating behaviour to make real change. He explains how the most creative thinkers, forward-looking entrepreneurs, and influential change agents in every sector of our society harness the power of their imaginations to achieve their goals. He outlines how the best leaders also show others how to use their imaginations to expand their individual and collective potential. The Imagination Gap helps leaders in every sector apply their imaginations to explore new, creative approaches to help them survive and thrive. The book features in-depth interviews and examples from a range of industries and settings with guidance and steps on how to stop thinking the way you "should" and start making extraordinary things happen.